Chalepin and Chalepensin: Occurrence, Biosynthesis and Therapeutic Potential - Nahar, Lutfun; Al-Majmaie, Shaymaa; Al-Groshi, Afaf; Rasul, Azhar; Sarker, Satyajit D (Molecules (Basel, Switzerland), 2021)
Dihydrofuranocoumarin, chalepin (1) and furanocoumarin, chalepensin (2) are 3-prenylated bioactive coumarins, first isolated from the well-known medicinal plant Ruta chalepensis L. (Fam: Rutaceae) but also distributed in various species of the genera Boenminghausenia, Clausena and Ruta. The distribution of these compounds appears to be restricted to the plants of the family Rutaceae. To date, there have been a considerable number of bioactivity studies performed on coumarins 1 and 2, which include their anticancer, antidiabetic, antifertility, antimicrobial, antiplatelet aggregation, antiprotozoal, antiviral and calcium antagonistic properties. This review article presents a critical appraisal of publications on bioactivity of these 3-prenylated coumarins in the light of their feasibility as novel therapeutic agents and investigate their natural distribution in the plant kingdom, as well as a plausible biosynthetic route.
Keywords: Animals; Clausena; chalepin; rostlinné extrakty; Furocoumarins; lidé; Rutaceae; Coumarins; bioactivity; chalepensin; Ruta chalepensis; léčivé rostliny; kumariny; Plant Extracts; Plants, Medicinal; zvířata; biosynthesis; Ruta; furokumariny; Humans